Currently, The Problems Of the Process Of Moistening Raw Cotton and Cotton Fiber (Texas Journal of Engineering and Technology, 2025)
The moistening of raw cotton and cotton fiber is a critical stage in the textile production process, significantly influencing the quality of the final product. However, achieving optimal moisture content presents numerous challenges. One of the primary problems is the uneven distribution of moisture during processing, which can lead to variations in fiber strength and quality. The inappropriate application of water or humidification methods often causes fiber shrinkage, reduced durability, and increased contamination. Furthermore, the control of temperature and humidity plays a vital role in preventing over-drying or excessive moisture retention, both of which can negatively affect the spinning and handling properties of cotton fibers. Technological limitations, coupled with the complexity of monitoring moisture levels accurately, result in inefficiencies in the cotton processing industry. Research has also shown that improper moisture regulation can lead to decreased efficiency in machinery, increased energy consumption, and a higher likelihood of fiber damage during transportation and storage. Therefore, addressing these issues requires advancements in moisture control technologies and the development of standardized procedures to ensure consistent and high-quality cotton fiber production